Tasawuf Humanistik dan Relevansinya terhadap Kehidupan Sosial Spiritual Masyarakat Post Modern Abad Global (Telaah Atas Pemikiran Tasawuf Said Aqil Siradj dan Muh. Amin Syukur) - Muhamad Basyrul Muvid; Akhmad Fikri Haykal (Refleksi, 2020)
The modern era which is now stepping on the industrial revolution 4.0 era has caused the human condition to change rapidly, they are “tempted” by technological sophistication so that they slowly forget and leave religion (God) which ultimately leads to social and spiritual problems in the midst of society in addition to moral problems that cannot be solved with any technological sophistication. The focus of this research is to analyze and find a solution to solve this problem through the concept of humanistic Sufism which was initiated by Said Aqil Siradj and Muh Amin Syukur. The findings produced are that humanistic Sufism Said Aqil and Amin Syukur are Sufism that teaches humans to be active in social life, pro-active to social problems, politics, economics, nationality, please help, tolerance, as well as to draw closer to God continuously. Humanistic Sufism also teaches to synergize between the world-hereafter, the soul-body, inner-soul, God-creature, social-individual, Sharia-nature. It is this moderate attitude which seeks to develop humanistic Sufism which later leads to the formation of social piety and spiritual piety that very relevant to the life of post modern people who are currently experiencing a social and spiritual crisis.